Use of DInSAR Data for Multi-level Vulnerability Assessment of Urban Settings Affected by Slow-moving and Intermittent Landslides. (2016) - Infante, Donato; Confuorto, Pierluigi; Di Martire, Diego; Ramondini, Massimo; Calcaterra, Domenico
Abstract: The paper shows an innovative methodology which can be used to forecast the spatial and temporal evolution of the buildings' structural vulnerability in urban settlements affected by slow-moving intermittent landslides. Multi-level and integrated analysis, of conventional and innovative monitoring techniques with structural analysis methods for damage assessment allows to estimate, at different levels of accuracy, future conditions of damage and local failures of single buildings and building aggregates. To this purpose, in the last decade, Satellite Radar Interferometry and in particular the Differential SAR Interferometry (DInSAR) technique has been successfully applied as a remote-sensing tool in several analyses aimed at prediction and mitigation of buildings' damage induced by slow-moving landslides. The proposed methodology has been here applied to the urban settlement of Moio della Civitella (Salerno province, Italy).